Language Documentation on Local Culinary of Oa-Cusse Ambeno, Timor Leste - I Gusti Ayu Agung Dian Susanthi; Mirsa Umiyati (Warmadewa Press, 2021)
Traditional culinary is a representation of a society that becomes a cultural identity. With the presence of these traditional culinary delights, it can be a means of introducing social, cultural and tourism life. As with other countries, Timor Leste is rich in cuisine, especially traditional culinary delights that have a big role in preserving the lives of its people. Basically, food does not only focus on consumption but also enhances the image of society and informs the condition of the people. In this case, the Master of Linguistics at Warmadewa University collaborates with Escolla TÑcnica Vocacional Publico De Palaban, Pante-Macassar, Oa-Cusse Ambeno, Timor Leste which through this international community service activity held a socialization in the form of preservation of traditional Timorese culinary by presenting the community, especially the generation young people for the introduction of tools, materials and procedures for making traditional culinary delights and their relation to linguistics in the form of vocabulary. This study shows the interest of the younger generation in their efforts to preserve traditional culinary delights. This research uses a case study research type to get maximum results. The results of this service state that the community, especially the younger generation, can follow the socialization well and understand the procedures for making traditional culinary delights and are able to name the types of food and describe each procedure.